Therapeutic Potential of HGF-Expressing Human Umbilical Cord Mesenchymal Stem Cells in Mice with Acute Liver Failure - Yunxia Tang; Qiongshu Li; Fanwei Meng; Xingyu Huang; Chan Li; Xin Zhou; Xiaoping Zeng; Yixin He; Jia Liu; Xiang Hu; Ji-Fan Hu; Tao Li (International Journal of Hepatology)
Human umbilical cord-derived mesenchymal stem cells (UCMSCs) are particularly attractive cells for cellular and gene therapy in acute liver failure (ALF). However, the efficacy of this cell therapy in animal studies needs to be significantly improved before it can be translated into clinics. In this study, we investigated the therapeutic potential of UCMSCs that overexpress hepatocyte growth factor (HGF) in an acetaminophen-induced acute liver failure mouse model. We found that the HGF-UCMSC cell therapy protected animals from acute liver failure by reducing liver damage and prolonging animal survival. The therapeutic effect of HGF-UCMSCs was associated with the increment in serum glutathione (GSH) and hepatic enzymes that maintain redox homeostasis, including γ-glutamylcysteine synthetase (γ-GCS), superoxide dismutase (SOD), and catalase (CAT). Immunohistochemical staining confirmed that HGF-UCMSCs were mobilized to the injured areas of the liver. Additionally, HGF-UCMSCs modulated apoptosis by upregulating the antiapoptotic Bcl2 and downregulating proapoptotic genes, including Bax and TNFα. Taken together, these data suggest that ectopic expression of HGF in UCMSCs protects animals from acetaminophen-induced acute liver failure through antiapoptosis and antioxidation mechanisms.